PENGARUH PROGRAM GERAKAN LITERSI SEKOLAH (GLS) TERHADAP MINAT BACA DAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR - Zainuddin ,; Hikma Fausiah; Hasrianti . (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2023)
This research discusses the influence of the School Literacy Movement (GLS) program on the reading interest and writing skills of elementary school students in Indonesia. The purpose of this study is (1) to determine the influence of the School Literacy Movement (GLS) program on the reading interest of elementary school students, (2) to determine the influence of the School Literacy Movement (GLS) program on the writing skills of elementary school students. The method used in preparing this article is a literature study using reference materials in journal articles. The data collection techniques are documentation and data analysis processes using content analysis methods. The results showed a significant influence of the School Literacy Movement (GLS) program on elementary school students reading interests and writing skills. Keywords: school literacy movement, interest in reading, writing skills